Alternate forms of the Coupled Leakage Model - Schultz, C. P. (2013 IEEE Aerospace Conference, 2013)
The original Coupled Leakage Model of a multiple winding transformer embodies the subject magnetic circuit by magnetically coupling the secondary referenced leakage inductances. Leakage inductance is included in each of the multiple secondary windings, however this model introduced an effective coupling coefficient between the leakages. The model is further extended here to show that it fully supports alternate forms whereby the leakage inductance can be reflected in part, or in total, into the primary winding. Experimental and circuit simulation results are included to verify these alternate forms of the model. Lastly, a two winding version of the Coupled Leakage Model is compared to an existing two winding model in order to illustrate other differences.